The islanders - Christopher Priest (Gollancz, 2011)
"The Dream Archipelago is a vast network of islands. The names of the islands are different depending on who you talk to, their very locations seem to twist and shift. Some islands have been sculpted into vast musical instruments, others are home to lethal creatures, others the playground for high society. Hot winds blow across the archipelago and a war fought between two distant continents is played out across its waters"--Cover. Read less